An investigation into domino-Heck reactions of N-acylamino-substituted tricyclic imides:: Synthesis of new prospective pharmaceuticals - Bagdatli, Emine; Ocal, Nueket; Kaufmann, Dieter E. (WILEY-V C H VERLAG GMBH, 2007)
Heck and domino-Heck reactions of unsaturated N-acylamino-substituted tricyclic imides with aryl(heteroaryl) iodides and phenyl- or (trimethylsilyl)acetylene were either carried out in the presence of formate or phenyl- and (trimethylsilyl) acetylene, respectively. The C-C coupling reactions appeared to be completely diastereoselective, giving the corresponding N-acylamino-5-exo-aryl (heteroaryl)- (5a-c, 6a,b),N-(benzoylamino)-5-exo-phenyl-6-exo-[(trimethylsilyl)ethynyl]- (5d), or 5-exo-(4-chlorophenyl)-N-(2,2-dimethylpropanoylamino)-6-exo-(phenylethynyl)bicyclo[2.2.1]heptane-2-endo,3-endo-dicar- boximide (6c) (Schenzes 3 and 4).
Keywords: PALLADIUM-CATALYZED REACTIONS; CYCLIC IMIDES; EPIBATIDINE; CHEMISTRY; LIGAND